The Changing Role of the Hospital in European Health Systems - McKee, Martin; Merkur, Sherry; Edwards, Nigel; Nolte, Ellen (Social Sciences, 2020)
Hospitals must change in the face of changing technologies and patient needs. This book is for anyone who works in a hospital, giving them the evidence they need to call for change, and for policy makers and planners charged with designing and operating hospitals now and in the future.